2021
DOI: 10.21203/rs.3.rs-268729/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Management of chronic lung diseases in Sudan and Tanzania: how ready are the country health systems?

Abstract: BackgroundChronic Lung Diseases (CLDs), responsible for 4 million deaths globally every year, are increasingly important in low- and middle-income countries where most of the global mortality due to CLDs currently occurs. As existing health systems in resource-poor contexts, especially sub-Saharan Africa (SSA), are not generally oriented to provide quality care for chronic diseases, a first step in re-imagining them is to critically consider readiness for service delivery across all aspects of the existing sys… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The availability of SABA inhalers was described in 23 countries but only six countries reported an availability of 80% or more at any of their study sites (table 2, figure 2). [24][25][26]38 The availability of SABA inhalers ranged widely, from unavailable in Bhutan to 100% in Eritrea. 25 One study reported that generic SABA inhalers were more widely available than originator brands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of SABA inhalers was described in 23 countries but only six countries reported an availability of 80% or more at any of their study sites (table 2, figure 2). [24][25][26]38 The availability of SABA inhalers ranged widely, from unavailable in Bhutan to 100% in Eritrea. 25 One study reported that generic SABA inhalers were more widely available than originator brands.…”
Section: Resultsmentioning
confidence: 99%
“…41,46 The availability of SABA nebules ranged from 10•0% in Tanzania to 58•8% in Nigeria. 26,41 Antimuscarinic agents were not available in several countries including Benin, Eritrea, Bhutan, Viet Nam, and Ghana, but were available in 30•8% of facilities in Sri Lanka. 25,28,39 The only data on antimuscarinic nebules came from Nigeria and The Gambia, where availability ranged between 0•0% and 13•0%.…”
Section: Resultsmentioning
confidence: 99%
“…A study of health system preparedness for managing chronic lung diseases in Sudan and Tanzania identified the lack of access to PEF meters for diagnostic purposes as an important barrier to care. [35]…”
Section: Limited Access To Diagnostic Testsmentioning
confidence: 99%
“…Sudan and Tanzania were selected for the IMPALA's health systems research work package . Our baseline situation analysis in Dodoma region of Tanzania and Gezira state in Sudan explored the readiness of health facilities in these areas to deliver care for CRD (5). Both sites are mainly rural and semi-urban, with inhabitants engaged mostly in informal livelihoods.…”
Section: Study Sites and Contextmentioning
confidence: 99%
“…In sub-Saharan Africa (SSA), the increasing burden is driven by indoor air pollution due to domestic use of biomass fuel, which is used for cooking by approximately 90% of rural households(3); tobacco smoke; and post tuberculosis lung disease (4). Despite increasing recognition, CRDs are rarely prioritised by communities, health systems, or governments in SSA and robust data with which to inform CRD interventions are lacking (5). Reliable data on the prevalence of CRDs in Sub Saharan Africa (SSA) are scarce.…”
Section: Introductionmentioning
confidence: 99%